Fintech: finance, technology and regulation - REMOLINA, Nydia (Institutional Knowledge at Singapore Management University, 2024)
Fintech: finance, technology and regulation, by Ross P. Buckley, Douglas W. Arner,and Dirk A. Zetzsche, Cambridge, Cambridge University Press, 2024, 330 pp, £29.99(paperback), ISBN 978-1-009-07821-4